Extreme sleep fragmentation for 11 consecutive days and nights does not significantly alter total sleep time, and sleep stage distribution, during the continuous alpine downhill skiing world record - Mirco Gindulis; Nikolaus Netzer; Martin Burtscher; Hannes Gatterer; Christian Schmidt; Audry Morrison; Thomas Küpper (University of Applied Sciences in Tarnow, Poland, 2021)
Introduction: Extreme levels of sleep deprivation, fragmentation and management, are major problems in many sportive disciplines, ultramarathons, polar or extreme altitude expeditions, and in space operations. Material and methods: Polysomnographic (PSG) data was continuously recorded (total sleep time and sleep stage distribution) in a 34-year-old male whilst performing the new world record in long-term downhill skiing. He napped only during the short ski lift rides for 11 days and nights. Results: After an initial period of complete sleep deprivation for 24 hours, total sleep time and the total times of non-REM and REM achieved during the lift rides returned to standard values on the second day. PSG data revealed an average sleep time per 24 hours of 6 hours and 6 minutes. During daylight sleep was rarely registered. The subject experienced only two minor falls without injury and immediately resumed skiing. Conclusion: In a healthy, trained, elite male athlete, sleep fragmentation over 11 consecutive days did not significantly impair the sleep, motor or cognitive skills required to perform a continuous downhill skiing world record after an initial adaptation phase